P-84 Subjective and objective chemosensory (taste and smell) dysfunction in treatment-naive cancer patients. (1st March 2017) - Barrett, Michelle; Dhuibhir, Pauline U; O'Donoghue, Niamh; Gilham, Charles; Beltagi, Nazmi El; Walsh, Declan
Abstract : Background: Chemosensory dysfunction (CD; a defect in taste and/or smell) in cancer is associated with chemotherapy and radiotherapy or may occur as a result of cancer itself. CD can increase risk of weight loss and malnutrition as a result of food aversions and reduced dietary intake. Aims: To subjectively and objectively assess taste and smell in newly diagnosed non-head and neck cancer patients. To examine nutritional status in those with taste and smell changes. Methods: Consecutive pre-treatment cancer patients were recruited from radiation oncology clinics in a prospective observational study. A 12-item Taste and Smell Questionnaire evaluated the presence, severity and characteristics of taste and smell dysfunction and the Abridged Patient-Generated Subjective Global Assessment (abPG-SGA) measured nutritional status and symptoms. Burghart Taste Strips ® and 'Sniffen' Sticks Olfactory Test ® assessed taste and smell identification. Results: Twenty newly diagnosed (<3 months) patients were recruited. Diagnoses included breast cancer (9) gynaecological cancer (7) and colorectal cancer (4). Over half (n=12, 60%) reported subjective taste and/or smell changes or had abnormal objective tests. Of these, six reported taste and smell changes (TSC), two taste only and one smell only. Nine were identified as being at risk of malnutrition (abPG-SGA score ≥6). Four of them reported subjective taste or smell changes only while another two had both subjective and objective changes. Conclusions: Subjective and objective taste and smell testing were well tolerated. The majority of patients had subjective or objective TSC abnormalities before treatment. This is consistent with a previous study. Subjective assessment identified more TSC than objective. Those with TSC appeared to be at higher risk of malnutrition.